Deposit Insurance, Regulation, and Moral Hazard in the Thrift Industry: Evidence from the 1930's - Grossman, Richard S. (American Economic Review, 1992)
This paper compares risk-taking of insured and uninsured thrifts operating under strict and less-strict regulatory regimes during the 1930's. Analysis of balance-sheet data indicates that while newly insured thrifts undertook less risk than their uninsured counterparts, possibly because of screening by deposit-insurance authorities, moral hazard emerged gradually. Insured institutions operating under relatively permissive regulatory regimes were more prone to undertake risky lending activities than their more tightly regulated counterparts. Given the current system of deposit insurance, the results suggest that effective regulation and supervision will play a key role in maintaining thrift stability in the 1990's.